External validation of the ITA.LI.CA prognostic system for patients with hepatocellular carcinoma: A multicenter cohort study. Issue 6 (19th April 2018) - Borzio, Mauro; Dionigi, Elena; Rossini, Angelo; Marignani, Massimo; Sacco, Rodolfo; De Sio, Ilario; Bertolini, Emanuela; Francica, Giampiero; Giacomin, Anna; Parisi, Giancarlo; Vicari, Susanna; Toldi, Anna; et al.
Abstract : Several staging systems for hepatocellular carcinoma (HCC) have been developed. The Barcelona Clinic Liver Cancer staging system is considered the best in predicting survival, although limitations have emerged. Recently, the Italian Liver Cancer (ITA.LI.CA) prognostic system, integrating ITA.LI.CA tumor staging (stages 0, A, B1‐3, C) with the Child‐Turcotte‐Pugh score, Eastern Cooperative Oncology Group performance status, and alpha‐fetoprotein with a strong ability to predict survival, was proposed. The aim of our study was to provide an external validation of the ITA.LI.CA system in an independent real‐life occidental cohort of HCCs. From September 2008 to April 2016, 1, 508 patients with cirrhosis and incident HCC were consecutively enrolled in 27 Italian institutions. Clinical, tumor, and treatment‐related variables were collected, and patients were stratified according to scores of the Barcelona Clinic Liver Cancer system, ITA.LI.CA prognostic system, Hong Kong Liver Cancer system, Cancer of the Liver Italian Program, Japanese Integrated System, and model to estimate survival in ambulatory patients with hepatocellular carcinoma. Harrell's C‐index, Akaike information criterion, and likelihood‐ratio test were used to compare the predictive ability of the different systems. A subgroup analysis for treatment category (curative versus palliative) was performed. Median follow‐up was 44 months (interquartile range, 23‐63 months), and median overall survival was 34 months (interquartile range, 13‐82 months). Median age was 71 years, and patients were mainly male individuals and hepatitis C virus carriers. According to ITA.LI.CA tumor staging, 246 patients were in stage 0, 472 were in stage A, 657 were in stages B1/3, and 133 were in stage C. The ITA.LI.CA prognostic system showed the best discriminatory ability (C‐index = 0.77) and monotonicity of gradients compared to other systems, and its superiority was also confirmed after stratification for treatment strategy. Conclusion : This is the first study that independently validated the ITA.LI.CA prognostic system in a large cohort of Western patients with incident HCCs. The ITA.LI.CA system performed better than other multidimensional prognostic systems, even after stratification by curative or palliative treatment. This new system appears to be particularly useful for predicting individual HCC prognosis in clinical practice. (Hepatology 2018;67:2215‐2225)